Effect of Different Coating Elements on Shelf Life of Indian Olive (Elaeocarpus floribundus Blume) - Misra, Sukanya; Chattopadhayay, Priyam; Paul, Prodyut kr. (International Journal of Bio-resource and Stress Management, 2019)
The experiment was conducted during 2015–16 in the laboratory of Department of Pomology and Postharvest Technology, Horticulture, Uttar Banga Krishi Viswavidyalaya to study the effect of different Coating elements on shelf life of Indian Olive (Elaeocarpus floribundus Blume). Among 13 different treatments, spoilage % was minimum in Guar gum and highest (65%) occurred in Control. At the end of storage weight loss of chitosan treated fruits were lower than the other treatments, in control it was 47.09%. A combination treatment of paraffin liquid and calcium chloride and uncoated fruits resulted in highest disease incidence (30%). At the last day of storage lowest (6.04%) total sugar percentage was seen in Control whereas highest (6.29%) was seen in CaCl2 and Guar gum treated fruit. Reducing sugar was found lowest (3.19%) in Calcium chloride (2%) (w/v)+Paraffin liquid (5%)(v/v) and Calcium chloride (2%) (w/v)+Chitosan (2%) (w/v), where as highest reducing sugar was seen in Calcium chloride (1%)(w/v)+Paraffin liquid (5%)(v/v) at the final day of storage. The maximum (3.01%) non-reducing sugar was found in Gum tragacanth (2%) followed by Calcium chloride (2%) (w/v)+Paraffin liquid (5%)(3.01%) and the lowest (2.74%) was seen in Calcium chloride (1%)(w/v)+Paraffin liquid (5%)(v/v). Ascorbic acid was highest (20.86 g 100 g-1 of pulp) in Calcium chloride (2%) (w/v)+Chitosan (2%)(w/v) and Calcium chloride (2%) (w/v)+Parafin liquid and it was lowest (18.2 g 100 g of pulp-1) in Control.The lowest (1.25%) acid content was present in Calcium chloride (2%) (w/v)+Guar gum (2%) (w/v), highest (1.93%) was seen in Calcium chloride (1%) (w/v)+Chitosan (2%)(w/v). Maximum (387.633 g) penetration force was seen in Calcium chloride (1%) (w/v)+Guar gum (2%) (w/v) and minimum (241.067 g) was in Control.